2017
DOI: 10.1371/journal.pone.0186762
|View full text |Cite|
|
Sign up to set email alerts
|

Body-size structure of Central Iberian mammal fauna reveals semidesertic conditions during the middle Miocene Global Cooling Event

Abstract: We developed new quantitative palaeoclimatic inference models based on the body-size structure of mammal faunas from the Old World tropics and applied them to the Somosaguas fossil site (middle Miocene, central Iberian Peninsula). Twenty-six mammal species have been described at this site, including proboscideans, ungulates, carnivores, insectivores, lagomorphs and rodents. Our analyses were based on multivariate and bivariate regression models correlating climatic data and body-size structure of 63 modern mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 104 publications
0
4
0
7
Order By: Relevance
“…A small reorganization of the amphicyonid fauna thus occurred between MN5 and MN6. This biotic event might be related to the Middle Miocene Climatic Transition ( Steinthorsdottir et al, 2021 ), which results for instance in an increase in aridity in Spain ( Menéndez et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A small reorganization of the amphicyonid fauna thus occurred between MN5 and MN6. This biotic event might be related to the Middle Miocene Climatic Transition ( Steinthorsdottir et al, 2021 ), which results for instance in an increase in aridity in Spain ( Menéndez et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Heteroprox, as most cervids, inhabited forested areas (López-Martínez et al 2000). While the other Eurasian Heteroprox species were known to live in humid forests, the conditions during the Middle Miocene in much of the Central Iberian Peninsula were significantly arid or even semi-desertic (Fesharaki 2016;Menéndez et al 2017). Therefore, the habitats of H. moralesi were most likely forest patches near savannas and arid environments.…”
Section: Resultsmentioning
confidence: 99%
“…Atlantoxerus has an extant re p resentative (Barbary ground squirrel, A. getulus) that lives in African deserts (Van Dam & Weltje 1999, Minwer Barakat 2005, GarcíaAlix et al 2008, Mansino et al 2018. According to MinwerBarakat (2005) andGarcía Alix et al (2008) these genera are associated to open and denuded environments, and Menéndez et al (2017) have reported the species H. rubricati in the semidesertic habitat of the site Somosaguas in the Madrid Basin. Aragoxerus might have shared these preferences, although there is no literature on this topic, but CuencaBescós (1988) or Denys et al (2003), among others, include this genus in the Xerini, that generally have a similar life style.…”
Section: Palaeoecologymentioning
confidence: 99%